Si-Wu-Tang improves liver fibrosis by restoring liver sinusoidal endothelial cell functionality and reducing communication with hepatic stellate cells - Le Wang; Jiaorong Qu; Jianan Li; Xiaoyong Xue; Lingling Qin; Yufei Li; Yuanfeng Dou; Xiaohong Mu; Xiaojiaoyang Li (Chinese Medicine)
Abstract Background Liver fibrosis is a complex reparative process in response to chronic liver injuries, with limited effective therapeutic options available in clinical practice. During liver fibrosis, liver sinusoidal endothelial cells (LSECs) undergo phenotypic changes and also play a role in modulating cellular communications. Si-Wu-Tang (SWT), a traditional Chinese herbal remedy, has been extensively studied for its effectiveness in treating hematological, gynecological and hepatic diseases. Materials and methods The component of SWT were identified by ultra-high-performance liquid chromatography (UHPLC). After establishing bile duct ligation (BDL)-induced liver fibrosis mice model and VEGFA-stimulated LSEC model, we invested the mechanism of SWT through RNA sequencing combined with molecular biology techniques. Results SWT significantly improved the sinusoidal permeability and liver fibrosis induced by BDL and effectively regulated pathological processes in LSECs, such as angiogenesis, cell adhesion, basement membrane formation and defenestration. The anti-fibrosis effects of SWT were attributed to the inhibition on LSEC adhesion via COL8A1, on LSEC angiogenesis via IL-1β and the induction of LSEC defenestration by OLR1. Additionally, SWT disrupted the intercellular crosstalk between LSECs and hepatic stellate cells (HSCs) driven by IL-1β, thus alleviating liver fibrosis. Conclusion SWT collectively ameliorated liver fibrosis by inhibiting the COL8A1/IL-1β/OLR1 pathways associated with LSEC angiogenesis, adhesion and defenestration, as well as suppressing LSEC secretion of IL-1β to reduce HSC activation.